Efeitos da performance ESG no custo de capital próprio e assimetria informacional no mercado de capitais brasileiro - Cirne, Gianinni Martins Pereira (Universidade do Vale do Rio dos Sinos, 2023)
Corporate actions focused on ESG issues grew a lot, and gained visibility. The term refers to corporate sustainability practices that relate the Environment (Environmental), Social (Social) and Governance (Governance). With the growth of investment in ESG practices, questions have arisen about their impact on companies, given this scenario, this research aims to analyze the effect of ESG practices on the cost of equity and information asymmetry of companies in the Brazilian capital market. We innovated when we incorporated ESG performance as a moderating variable in the relationship between information asymmetry and cost of equity. Allied to this, we use a CAPM calculation model adjusted to the reality of emerging countries. Our result showed that ESG performance really has an effect on information asymmetry and moderates the relationship with the cost of equity capital, as the result found showed that there was an impact on the reduction of the cost of equity capital when we tested the moderating effect, that is, ESG performance reduced information asymmetry and consequently reduced the cost of equity. We tested our dataset with the traditional CAPM model, and the results were different from an adjusted model, leading us to conclude the relevance of adjusting valuation models to the reality of emerging economies. Based on the foregoing, the defended thesis is confirmed that companies in the Brazilian capital market, which are part of the ESG performance rating, have a lower cost of equity due to the reduction of information asymmetry, influenced by ESG performance.
Keywords: Rating por performance ESG; Economias emergentes; Assimetria de informações; Efeito moderador; Rating ESG performance; Emerging economies; Information asymmetry; Moderating effect; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis